Disciplined entrepreneurship workbook - Aulet, Bill, 1958- (Online access with DDA: Askews (Economics), 2017)
The essential companion to the book that revolutionized entrepreneurship Disciplined Entrepreneurship Workbook provides a practical manual for working the 24-step framework presented in Disciplined Entrepreneurship. Unlocking key lessons and breaking down the steps, this book helps you delve deeper into the framework to get your business up and running with a greater chance for success. You'll find the tools you need to sharpen your instinct, engage your creativity, work through hardship, and give the people what they want--even if they don't yet know that they want it. Real-world examples illustrate the framework in action, and case studies highlight critical points that can make or break you when your goal is on the line. Exercises and assessments help you nail down your strengths, while pointing out areas that could benefit from reinforcement--because when it comes to your business, "good enough" isn't good enough--better is always better. Disciplined Entrepreneurship transformed the way that professionals think about starting a company, and this book helps you dig into the proven framework to make your business dreams a reality. Delve deeper into the 24 steps to success Innovate, persevere, and create the product people want Internalize lessons learned from real-world entrepreneurs. Test your understanding with exercises and case studies. The book also includes new material on topics the author has found to be extremely useful in getting the most value out of the framework including Primary Market Research, Windows of Opportunity and Triggers. The book also introduces the Disciplined Entrepreneurship Canvas to track your progress on this journey. Starting a company is a serious undertaking, with plenty of risk and sacrifice to go around--so why not minimize the risk and make the outcome worth the sacrifice? Author Bill Aulet's 24-step framework is proven to build a successful business; the key is in how well you implement it. Disciplined Entrepreneurship Workbook helps you master the skills, tools, and mindset you need to get on your path to success.